INTERAKSI ANTARA GAYA AKSIAL DAN MOMEN PADA KOLOM BETON DENGAN TULANGAN BAMBU - Sutarja, I Nyoman; Sudarsana, I Ketut (Jurnal Ilmiah Teknik Sipil, 2012)
The use of bamboo reinforcement in reinforced concrete structure has not been investigated extensively. The material is expected as an alternative of steel reinforcement in a certain condition. Therefore, this research is conducted to investigate the capacity of columns reinforcing using bamboo in term of their axial strength and moment as well as their interactions. Twelve columns reinforcing of bamboo are made and tested. Column dimensions of 150 mm x 150 mm x 900 mm were cast using 15 MPa concrete obtained from ASTM standard cylinder test of age of 28 days. Two group specimens based on its total reinforcement areas were made namely 400 mm2 and 600 mm2. Six variations were made for each group to incorporate variation of applied load eccentricities during the test. The load eccentricities were 0 (pure axial), 70 mm, 100 mm, 150 mm, 200 mm and ¥ (pure bending). Test results show that the experimental interaction between axial force and bending moment of the column reinforced with bamboo agree well with the analytical results following the expression for column reinforced with steel reinforcement. Taking the tensile strength of the bamboo 50% of the rupture strength, give the experimental column capacities were close to the analytical results.
Keywords: bamboo reinforcement, column, interaction diagram, reinforced concrete